Correlation between serum zinc level and simple febrile seizure in children - Lusiana Margaretha; Nurhayati Masloman (Paediatrica Indonesiana, 2016)
Background Simple febrile seizure is the most common form of seizure which occurs during childhood period. Zinc, one of microelements in human body, has an important role in central nervous system formation.